Pengaruh Pembelajaran Biologi Berbasis STEM terhadap Literasi Teknologi dan Keterampilan Pengambilan Keputusan Siswa SMA - Widodo, Ari; Rochintaniawati, Diana; Luthfiyani, Siti Halimatusya’diyyah (Assimilation: Indonesian Journal of Biology Education, 2019)
This study aims to analyze the effect of STEM-based biology learning on technological literacy and students’ decision making skills in senior high school. The sample used in this study were X grade students from two classes in one of the senior high school in Bandung. Determination of the research subject was carried out as a convenience sampling technique from recommendation teachers and studying the activities of students who had not learned about environmental pollution material. This study used a quasi-experimental method through a non-equivalent control group design. Student’s technological literacy in this study was measured by using several aspects of technological literacy while student’s decision making was measured by using open-ended questions that are relevant to socio-scientific issues. Student’s decision making analyzed based on the basic categories of decision making and the level of argumentation as a reasoning process in decision making. This study shows that STEM-based biology learning does not affect technological literacy and decision making in high school students. This was done on statistical tests on technological literacy and decision making skills tests results that showed no significant difference between students in STEM classes with non-STEM classes.